The psychosocial impact of wheelchair tennis on participants from developing countries. Issue 2 (16th January 2017) - Richardson, Emma V.; Papathomas, Anthony; Smith, Brett; Goosey-Tolfrey, Victoria L.
Abstract: Purpose : Individuals with physical disabilities in developing countries can experience many instances of psychosocial hardship. Although scholars have suggested that participation in sport can positively impact psychosocial health, few studies have explored this phenomenon within the disabled population of developing nations. Methods : Sixteen wheelchair tennis players were recruited across six developing countries and interviewed in regards to their experiences. Data were collected using semi-structured interviews, transcribed verbatim and subject to thematic analysis. Results : Wheelchair tennis players perceived their participation in sport enhanced their psychosocial well-being. Three broad themes emerged from analysis of the interviews; (1) developed transferrable skills, (2) perceived personal growth and (3) benefits of an athletic identity. Conclusions : Sports participation, in this case wheelchair tennis, may be a viable means to promote psychosocial well-being in disabled populations within developing nations. Moreover, sport holds the potential to challenge negative perceptions of disability at an individual and societal level within these cultures. Implication for Rehabilitation: Individuals with physical disabilities in developing countries may experience psychosocial hardship and cultural stigma. Wheelchair sport may be a viable means to enhance psychosocial well-being in this population. Skills learnt "on court" are transferrable to everyday life potentially improving independence and quality of life. Identifying as an athlete can challenge negative cultural perceptions of disability.